Ispas/ Psychology and Politics. - Ispas, Alexa (Taylor and Francis, 2012)
What makes us divide the world into 'us' and 'them'? How can we exert social influence over others? When does a peaceful protest turn into a riot? Why are some politicians heroes one day and villains the next? Where do we find the resources to resist authoritarian regimes?Taking these questions as a starting point, the book examines political conduct from a social identity perspective. Supported by over two decades of empirical research, this perspective distinguishes between our personal identity, which is prevalent when we think of ourselves as individuals, and our social id.